Analisis Penggunaan Aplikasi Kahoot sebagai Digital Game Based Learning dalam Evaluasi Pembelajaran PAI di SMA Negeri 2 Padang - Afiq Ma'ruf; Alfurqan Alfurqan (AS-SABIQUN, 2022)
The purpose of this study was to determine the process of using the Kahoot application as a digital-based game tool in the evaluation process of Islamic Religious Education learning at SMA Negeri 2 Padang. The development of technology is increasingly rapid, especially in the field of education, so teachers are required to be able to innovate, such as by utilizing technology as a means of learning media and as a learning evaluation tool. The Kahoot application is a web-based learning media or application that is used as an online-based evaluation process tool that makes it easier for teachers to increase student interest in participating in evaluation activities. Learning evaluation by utilizing the use of the Kahoot application is an alternative way that can be used by teachers to see the learning that has been carried out. This research applies qualitative research with the type of case study research, the data sources in this study consist of nine informants and documentation. The research methods used in this study were interviews, documentation, and observation. Data analysis with data reduction, data presentation, and concluding. For data analysis, the researcher applied the triangulation method by checking again. The results of this study prove that SMA Negeri 2 Padang has used the Kahoot application as a tool for the evaluation process in evaluating learning. The use of this Kahoot application still has some obstacles in its use. The use of this Kahoot application helps facilitate and becomes an attraction for students in the learning evaluation process activities.